Research regarding the influence of knowledge management practices on employee satisfaction in the Romanian healthcare system - Ion Popa; Simona Cătălina Ştefan; Cristina Morărescu; Claudiu Cicea (Amfiteatru Economic Journal, 2018)
The aim of this paper is to investigate the impact of knowledge management practices on healthcare system employees' satisfaction. A hypothesized causal model concerning the connections between three facets of knowledge management (knowledge acquisition, knowledge sharing, and knowledge utilization) and job satisfaction is proposed. A convenience sample of 459 respondents was chosen from 20 health organizations, including hospitals, pharmacies and medical centers providing specialized medical services. For the construction and validation of the econometric model and the validation of the research hypotheses, structural equation modeling (SEM) and technical support of IBM SPSS Amos 24.0 were used. The research results showed that knowledge acquisition and knowledge utilization have significant positive effects on employee satisfaction, while knowledge sharing is associated with a decrease in satisfaction. Moreover, relationships are moderated by the type of healthcare provided. In the end of the paper, theoretical and managerial implications are discussed.
Keywords: C3; D23; D83; I1; O34; 330; employee satisfaction; healthcare organization; knowledge management practices; knowledge acquisition; knowledge sharing; knowledge utilization